Mitochondrial genome of the Marbled goby (Oxyeleotris marmorata). (3rd March 2016) - Yang, Zhen-Yu; Liang, Hong-Wei; Li, Zhong; Wang, Dan; Zou, Gui-Wei
Abstract: The marble goby is a carnivorous fish native to freshwater in Asia-Pacific region, and it is marketed as a high-valued fish in some Asia countries such as China, Thailand and Vietnam. This study presents the complete mitochondrial genome of O. marmorata, which is 16, 525 bp length with the genome organization and gene order being identical to that of the typical vertebrate.